2011
DOI: 10.4061/2011/537821
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C and Toll-Like Receptor Signaling

Abstract: Protein kinase C (PKC) is a family of kinases that are implicated in a plethora of diseases, including cancer and cardiovascular disease. PKC isoforms can have different, and sometimes opposing, effects in these disease states. Toll-like receptors (TLRs) are a family of pattern recognition receptors that bind pathogens and stimulate the secretion of cytokines. It has long been known that PKC inhibitors reduce LPS-stimulated cytokine secretion by macrophages, linking PKC activation to TLR signaling. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 75 publications
9
99
0
Order By: Relevance
“…Several studies indicate that PKCs are involved in intracellular TLR signal transduction and activate the innate immune system leading to cytokine secretion. Further studies have shown that inhibition of PKC-␣ and PKC-␦ could retard the inflammatory responses in lung injury models (19). In this study, we found that inhibition of PKC with H7 decreased ICAM-1 expression induced by LPS (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies indicate that PKCs are involved in intracellular TLR signal transduction and activate the innate immune system leading to cytokine secretion. Further studies have shown that inhibition of PKC-␣ and PKC-␦ could retard the inflammatory responses in lung injury models (19). In this study, we found that inhibition of PKC with H7 decreased ICAM-1 expression induced by LPS (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…It is known that PKC serves as an upstream activator of MAP kinases. A549 (34), Beas2B (50), and THP-1 (18) cells express Toll-like receptor 4 (TLR4), and the signaling pathways activated by poultry dust extract, namely PKC, MAPKs, AP-1, and NF-B, are similar to those mediated via activation of TLR4 signaling pathway (32,33 MAPKs control IL-8 expression via transcriptional and mRNA stabilization mechanisms (21,60). MAPKs differentially regulate IL-8 expression depending on the cell type and the stimulus.…”
Section: Discussionmentioning
confidence: 96%
“…For example, enzymes from the protein kinase C (PKC) family, such as PKCε and PKCd, can associate with different adaptor proteins that are recruited to TLR4 (32,33). Activation of PKCs requires phosphorylation and enhanced levels of DAG, and the action of these kinases affects TLR4 downstream pathways such as MAPK activation, which ensures full production of inflammatory factors (34). Our studies support a scenario whereby lipin-1, by regulating DAG levels and the activation of upstream effectors like PKC, regulates TLR4 downstream signaling.…”
Section: Discussionmentioning
confidence: 99%